Study of the properties of chemically resistant repair mortar with the use of secondary raw materials. Issue 1 (December 2021) - Figala, P; Drochytka, R; Hermann, R
Abstract: This paper deals with the research of a new silicate-based repair mortar modified with selected secondary raw materials. The aim of this work is to develop a chemically resistant material suitable for use in an extremely aggressive environment of sewers. The monitored parameters include key physical-mechanical characteristics, resistance to sulphate ions and to the attack of aggressive biogenic sulfuric acid. Chemical resistance was tested by simulating the exposure environment in laboratory conditions, according to the methodology of DIN 19573. The obtained results show that by suitable modification of the reference mortar it is possible to maintain the values of physical-mechanical characteristics and improve the chemical resistance of test samples.